Window based personalized time management system - Siew Ann, Lilian Tong (2012)
The time management system is being widely used to manage time effectively.This paper presents on how window-based personalized time management system will be developed according to user’s need.Besides that,this paper will discuss on two(2)types of searching algorithm which are Binary Search Tree (BST) and Hashing Algorithm.The algorithms were tested and the one with better performance in terms of speed was implemented in this project.Through this system, users could manage their time in a simple and effective manner.